AN ANALYSIS USED IN BELIS TRADITION IN ANAKALANG, MIDDLE SUMBA - Hetti Susanti; Arining Wibowo; Trisno Tunggal Rahayu Wilujeng (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2015)
Belis tradition is part culture in Sumba and a condition to marriage someone. Many kinds of symbols used on it. Belis tradition is not separated from culture. By of culture, Belis be an own culture that has different process and symbols. Because every culture have different process based on that place. Therefore, the researcher has been interested in studying this problem by formulating four researcher problems such as: how the process of Belis tradition, what are the symbols and symbols meaning used in Belis tradition process, what kinds of terms used in Belis tradition?. There are so many symbols and terms used in Belis tradition. The symbols used such as sirih pinang, parang, gading, mamuli, stallion, pig, kombu cloth, rau nyau (janur), gong, kayu kaba (white cloth), and nibu pahori (spear). Every symbols has the meaning itself such as stallion as symbol of masculine. Sirih pinang as symbol of welcoming, and etc. And the terms used in Belis tradition such as year, layewa, ngaba wini, wunang, pahalaku hilu, kadehang, jedi, ahu papalu, and hangera. After the researcher found and discussed the problems of terms and symbols used in Belis tradition, the researcher made a conclusion of the research finding and discussion. From the result of this research, it was obvious that in Belis tradition used some symbols. And every symbol has own meaning. the researcher really hopes that this researcher to complete this study to be perfect. In addition, the researcher really hopes that this research can help other researcher who wants to continue or conduct research in the same field of the study or discuss about language aspect that occur in the Belis tradition especially in Anakalang.